4-ETOKSI-3-METOKSIFENOL DAN METIL-3,4-DIHIDROKSIBENZOAT, DUA SENYAWA TURUNAN FENOLIK DARI EKSTRAK ETIL ASETAT KULIT UMBI GADUNG (Dioscorea hispida Dennst) DAN AKTIVITAS ANTIOKSIDAN EKSTRAK ETIL ASETAT - Nanik Siti Aminah; Alfinda Novi Kristanti; Qonitah Labibah; Ana Firdausyah; Yoshiaki Takaya (Jurnal Kimia Riset, 2018)
Two phenolic compoundnamely 4-ethoxy-3-methoxyphenol and methyl-3,4-dihydroxybenzoic have been isolated fromDioscorea hispida Dennst. The isolation of phenolic compounds was done by maceration methods using methanol, followed by partition with n-hexane and ethyl acetate. The process of separation and purification used various chromatography techniques including vacuum liquid chromatography, column chromatography, and radial chromatography. The structure of isolated compounds were determined by spectroscopic methods including UV-Vis, IR, 1D and 2D NMR. The ethyl acetate extract was evaluated for DPPH free radical scavenging activity assay. The IC50of ethyl acetate extract was 415 ppm. The result of this assay indicated that ethyl acetate extract has a potential as an antioxidant.  Keywords: Dioscorea hispida Dennst, Dioscoreaceae, phenolic, 4-ethoxy-3-methoxyphenol, methyl-3,4-dihydroxybenzoic, and antioxidant